2020
DOI: 10.4067/s2452-55882020000200095
|View full text |Cite
|
Sign up to set email alerts
|

Giómeros fluidos en la eliminación de sensibilidad en molar permanente afectada con Hipomineralización Incisivo Molar (HIM). Reporte de caso.

Abstract: El principal motivo de consulta de los pacientes afectados con hipomineralización incisivo molar grado B 3 II, según la Academia Europea de Odontología Pediátrica (EAPO) es la estética y sensibilidad, provocando dolor a los cambios térmicos y a la hora de realizar el cepillado dental, esto puede conllevar a una rápida progresión de caries dental, por disminuir el cepillado. En el presente caso se describe la reconstrucción y sellado de fosas profundas de la pieza 46 afectada con hipomineralización incisivo mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…These studies were published between 2010 and 2022, and most of them come from Europe [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and Brazil [5,[28][29][30][31][32][33][34][35][36][37][38]. In terms of the included studies' design, 20 were case reports [8,13,15,16,19,[25][26][27]31,[33][34][35][38][39][40][41][42][43][44], 7 were cohort studies [14,18,20,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were published between 2010 and 2022, and most of them come from Europe [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and Brazil [5,[28][29][30][31][32][33][34][35][36][37][38]. In terms of the included studies' design, 20 were case reports [8,13,15,16,19,[25][26][27]31,[33][34][35][38][39][40][41][42][43][44], 7 were cohort studies [14,18,20,…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 38 included studies, 12 studies assessed glass ionomer cement and eight concluded that this material is "beneficial" [8,13,28,29,31,33,41,42], three studies concluded that it is "probably beneficial" [14,23,30], and one study concluded that its effects are "unclear" [26]. In terms of composite resin restorations, nine studies concluded that it is "beneficial" [18,19,21,24,27,34,38,40,44], one described it as "probably beneficial" [35], and two concluded that this material had "no effect" [5,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it does not appear to be a good alternative as a sealant in erupting teeth [48] . Positive results have also been reported for 7 months when used as a restoration in teeth with MIH including the elimination of sensitivity [49] . S-PRG cements used as pulp capping induce tertiary dentin [50] .…”
Section: Applications 351 Giomermentioning
confidence: 89%
“…Arce, [20] 2020 Case Report To describe the reconstruction, sealing of pits and fissures and eliminate sensitivity in a patient with MIH-affected teeth using giomer.…”
Section: Populationmentioning
confidence: 99%